Topical Tranexamic Acid in Total Knee Arthroplasty: Does It Augment the Effect of the Intravenous Administration in Patients with Moderate-to-High Risk of Bleeding? A Randomized Clinical Trial - Abdallah, Ahmed A.; Sallam, Asser A.; Arafa, Mohamed S.; Henawy, Ayman T. (The Journal of Knee Surgery, 2020)
This study aimed to compare the superimposed clinical value of topical tranexamic acid (TXA) application when it is simultaneously combined with intravenous (IV) administration versus the use of either IV TXA alone or IA TXA alone during primary total knee arthroplasty (TKA) in patients with moderate-to-high risk of bleeding. We hypothesized that the combined administration approach will result in a more adequate reduction in the perioperative blood loss and blood transfusion rate. Ninety-four patients undergoing primary TKA were randomly allocated into intra-articular (IA) alone, IV alone, and combined group. We used 2 g of IV TXA in the IV TXA alone and combined groups 10 minutes before tourniquet deflation. However, we applied 1.5 g TXA in 100 mL isotonic saline half topically before arthrotomy closure and half retrogradely after wound closure through the drain. Follow-up period was 6 weeks. The primary outcome measures included the drainage blood volume, total blood loss, hidden blood loss, intraoperative blood loss, and the allogenic transfusion rate. Secondary outcomes included postoperative hemoglobin drop, amount of transfused blood units, thromboembolism, and wound complications. Combined administration of TXA provided significantly better results in terms of blood volume collected by the drain, total blood loss, and hidden blood loss (p < 0.01). Contrarily, the intraoperative blood loss, the allogeneic transfusion rate, and the number of transfused units were similar in all groups (p > 0.05). The subgroup analysis revealed that a combined IA and IV TXA administration significantly reduced the total blood loss in patients with either moderate or high risk of bleeding. Moreover, the degree of hemoglobin drop was significantly lesser with the combined approach. No thromboembolic complications or wound infection occurred. In conclusion, the combined use of topical and IV tranexamic acid resulted in a significant reduction in postoperative blood loss and hemoglobin level following TKA but did not influence the rate of allogeneic blood transfusion. This is a Level I, therapeutic study.
Keywords: tranexamic acid; topical; intravenous; total knee arthroplasty; blood loss; antifibrinolytic drugs